(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the impact of artificial intelligence technologies on the modern educational process. The study comprehensively examines the positive and negative aspects of artificial intelligence in education, highlights the role and relevance of this technology in fundamentally changing the system. It also substantiates the importance of artificial intelligence in improving learning efficiency and improving assessment systems on a global scale.